An Analysis of Students’ Translation Quality in Translating Education-Related Public Notice - Indah Nilam Sari; Rusdi Noor Rosa (Universitas Negeri Padang, 2021)
The objective of this research are to find out the translation quality of students in translating notice and to find out the most difficult notice faced by students in term of accuracy from bahasa Indonesia into English. This study analyzed the translation quality of students from the quality aspects of accuracy, finding equivalence, translation skill, text function, and grammar & style. The data of this research was 15 notices collected from several schools in Padang. This research was conducted by using descriptive research and using translation test as an instrument collected from 40 students who have taken Indonesian-English Translation course in January-June 2020 of English department, Universitas Negeri Padang. To gain the trustworthiness of the research, this research applies the validator and the raters. The result shows that translation quality of students in translating notices was 70 in almost completely successful level. Furthermore, there were three notices which most difficult to translate by students in terms of accuracy.